Exploring the Effects of Cyberbullying on Empathy and Self-Worth: Insights from Victims and Offenders - Irmayanti, Nur; Eko Soetjipto, Budi; Chusniyah, Tutut; Rahmawati, Hetti (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The rapid advancement of information technology has expanded social interactions while simultaneously generating negative phenomena such as cyberbullying, which significantly affects individuals' psychological conditions. Cyberbullying can disrupt empathy and self-worth in both victims and offenders, making it essential to be explored comprehensively. This study aims to explore and analyze the effects of empathy and self-worth on involvement in cyberbullying from the perspectives of victims and offenders. A quantitative survey method was employed, using random sampling techniques to recruit 950 high school students as participants. Data were collected through standardized instruments measuring empathy and self-worth, and analyzed using Structural Equation Modeling (SEM). The findings revealed that empathy significantly influenced involvement in cyberbullying; individuals with higher empathy levels were more likely to become victims (β = 0.321, p = 0.003) but less likely to become offenders (β = -0.048, p = 0.044). In contrast, self-worth had a significant effect on victim involvement (β = 0.264, p = 0.003) but showed no significant relationship with offenders (β = 0.011, p = 0.647). These results indicate that empathy functions as a protective factor against becoming a cyberbullying offender while paradoxically increasing vulnerability to victimization. This study is expected to serve as a foundation for developing character-based intervention programs to prevent cyberbullying in educational environments.